1979
DOI: 10.2307/1268513
|View full text |Cite
|
Sign up to set email alerts
|

Designs for Mixture Experiments Involving Process Variables

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Published procedures for mixture experimentation in the presence of process variables are reviewed. Procedures which inscribe figures in the mixture space result in lower numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Hare [21]. Hare presents some design techniques which are useful when including process variables in mixture experiments.…”
Section: Designs For Mixtures Involving Process Variablesmentioning
confidence: 99%
“…Hare [21]. Hare presents some design techniques which are useful when including process variables in mixture experiments.…”
Section: Designs For Mixtures Involving Process Variablesmentioning
confidence: 99%
“…Alterações nos níveis dessas variáveis podem afetar o resultado experimental através de seus efeitos individuais e de interação com outras variáveis de mistura, mas seus níveis podem ser variados de forma independente. 12 Scheffé 7 e Hare 13 apresentaram trabalhos envolvendo delineamentos de misturas com variáveis de processo. Cornell e Deng 8 combinaram variáveis de processo com ingredientes de misturas em experimentos na área de alimentos.…”
Section: Introductionunclassified
“…The major ingredients in a chocolate peanut spread – peanut (P), chocolate (C) and sugar (S) – were combined to obtain a spreadable product using proportions of ingredients in a mixture design. In addition to the three mixture components, a processing variable (Cornell 1971; Hare 1979; Cornell 1990, 2000), roast (R), was included to study the effects of different roasting levels. It has been shown that roasting time has a significant influence on the odor and flavor of roasted peanuts (Buckholtz et al.…”
Section: Introductionmentioning
confidence: 99%